PET Hypometabolism of the Prefrontal-Cingulate Cortices in Internet Gaming Disorder - Kim, Sun Ki; Jeong, Hyeonseok; Im, Jooyeon Jamie; Lee, Sang Hoon; Chung, Yong-An (Frontiers in Psychiatry, 2021)
Recently, excessive and uncontrolled use of online games has been recognized as a public concern. Although previous neuroimaging studies have reported structural and functional brain deficits in Internet gaming disorder (IGD), very few studies have investigated the regional cerebral metabolic rate of glucose (rCMRglu). This study investigated the differences in rCMRglu between individuals with IGD and healthy controls using 18F-fluoro-2-deoxyglucose positron emission tomography (18F-FDG PET). A total of 23 adults with IGD and 23 controls underwent brain 18F-FDG PET scans and completed self-report questionnaires. A whole-brain voxel-wise analysis of rCMRglu was conducted and associations between rCMRglu and severity of IGD were assessed. The IGD group showed higher impulsivity (p = 0.04) and lower self-control (p = 0.002) than the control group. In addition, the IGD group had lower FDG uptake in the left medial orbitofrontal gyrus, left middle cingulate cortex, left superior frontal gyrus, and right anterior cingulate cortex (p < 0.001). A significant negative association was found between the rCMRglu in the right anterior cingulate cortex and the number of fulfilled diagnostic criteria for IGD (β = -0.50, p = 0.02). Our results suggest that IGD may be associated with deficits of glucose metabolism in the prefrontal-cingulate cortices.